Axial Compression Behavior of FRP Confined Laminated Timber Columns under Cyclic Loadings - Feng Shi; Libin Wang; Hao Du; Min Zhao; Hao Li; Feiqiu Wang; Shuangjun Wang (Buildings, 2022)
Fiber reinforced polymer (FRP) has been proved to be effective to improve the structural strength and ductility for column structures. An experimental study was conducted to investigate the compressive performance of FRP confined glued-laminated timber (GLT) and cross-laminated timber (CLT) columns. A total of 60 column specimens of two dimensions in height using different FRP types, FRP thickness, and laminate types were tested under cyclic axial compression loads. This study focuses on the compressive capacity and ductility of the new FRP composited timber structure. For this purpose, a loading protocol was designed, including a force-dependent pre-load and an amplitude-increasing displacement-dependent cyclic compression load. The results showed that the ultimate compression load of specimens was considerably promoted by the FRP sheets. Wrapping FRP sheets led to an average improvement of 29% and 24% for the FRP confined CLT and GLT specimens, respectively, compared to the initial stiffness of unreinforced specimens. Using the FRP sheets, the energy dissipation capacity of CLT and GLT specimens was increased by 358% and 266%, respectively. In general, GLT specimens had a higher energy dissipation rate compared to the CLT specimens, while CLT specimens showed a better potential for sustained energy consumption if confined with sufficient FRP sheets.